Effects of two resistance exercise programs on the health-related fitness of obese women with pain symptoms in the knees: Efectos de dos programas de ejercicios resistidos en la aptitud física relacionada con la salud de mujeres obesas con síntomas de algia en las rodillas - Rodrigues Cambiriba, Ayanne (2021)
Introduction: Overweight negatively impacts the cardiovascular system and osteomyoarticular, promoting pain in the joints of the lower limbs. Therefore, strategies have been applied to reduce overweight through lifestyle changes. Objective: to investigate the effects of two multidisciplinary intervention programs on the health-related physical fitness of obese women with pain symptoms in the knees. Methods: Women between 40 and 59 years of age with obesity (n=59) were evaluated in the pre- and post-intervention time regarding anthropometry, body composition, physical fitness, level of disability in the knee and hip, and health-related quality of life. A randomized clinical trial of parallel groups was conducted, using two resistance exercise programs and food re-education, for eight weeks. All participants received the same nutritional intervention content and for physical exercises were randomized into two groups, G1 being the "strength group" using machines (n=30), and G2 being the "functional training" group (n=29). Twenty-eight women (G1=18 + G2=10) were included in the final analyses. The groups and time were evaluated by two-way analysis of variance, with repeated measures. A p < 0.05 was assumed for all analyses. Results: a time effect was identified, with higher values for maximum isometric lumbar-traction strength (MILTS), after the intervention period in both groups (p < 0.05). However, for the other variables investigated, no significant differences were identified (p > 0.05). Conclusion: The absence of significant results for all variables, except FIMTL, may be justified by the moderate adherence of the participants to interventions (~59% to 66%) since the study was conducted during the period of social isolation (COVID-19). However, it is believed that the intervention models were positive in maintaining the variables studied.